A New Approach to Multivalued Certain Contraction Mappings - Aydın, Cafer; Yeşilkaya, Seher Sultan (Communications in Mathematics and Applications, 2020)
In the submit study, we establish the notion of generalization of partial Hausdorff metric space. Also, we state an extension of the concept of \(f\)-weak compatibility of Pathak [12] on metric space in generalization of partial metric space. We introduced some common fixed point theorems for multivalued mappings satisfying generalized weak contraction conditions on a complete \(G_p\) metric spaces. Also, a example is given to illustrate the main theorem. Further, our theorems generalize several formerly obtained fixed point results.
Keywords: Fixed point; \(f\)-weakly compatible mappings; \(G_p\)-metric space; Multivalued mappings